Impact dynamics and power-law scaling behavior of wet agglomerates - Thanh-Trung Vo (Computational Particle Mechanics, 2021)
We investigate the impact dynamics of a single wet agglomerate composed of primary spherical particles impacting a flat plane by using three-dimensional discrete element method simulations. The primary particle is assumed to be rigid and interacted with its near-neighboring particles by introducing approximate analytical expressions of capillary cohesion forces and lubrication forces induced from the liquid in addition to their elastic and frictional interactions. The paper analyzes the mechanical strength, the deformation, and the connectivity of wet particle agglomerate during the impact as well as in its early-stage impact and the final-stage deposition. We show that the mechanical strength, deformation, and connectivity of granule strongly depend on the key parameters (the liquid–vapor surface tension, the liquid viscosity, and the impact speed of agglomerate). In particular, the early-stage strength and the height of wet agglomerate at its final-stage deposition nicely behave as a function of the Capillary–Stokes inertial number that combines the Capillary number and Stokes number, and the macroscopic strength of the agglomerate at its early-stage impact has the microscopic origin from the normal compressive forces between primary particles. These observations are consistent that represent the relationship between the rheological properties and the liquid properties and the impact conditions of wet granular materials.